COMPARION OF GAP ARTHROPLASTY AND INTERPOSITIONAL GAP ARTHROPLASTY ON THE TEMPOROMANDIBULAR JOINT ANKYLOSIS - M. Ramezanian T. Yavary (Acta Medica Iranica, 2006)
Temporomandibular joint ankylosis causes limitation in mouth opening and establishes severe deformity and asymmetry in patient’s face, especially in children. Surgery is the only treatment. This study was conducted to compare the effect of two surgical approaches, gap arthropasty and interpositional gap arthroplasty, on rate of maximum interincisal opening in temporomandibular joint ankylosis. We also evaluated the relapse rate of these two surgical approaches. A total of 48 patients were enrolled in this cross-sectional experimental study. Range of mouth opening was evaluated before and during and one year after surgery. All other related information was also recorded. Mean age of the study population was 19.5  8.9 years. Of those, 21 (41%) were male and 27 (59%) were female. For 26 patients (54.2%) interpositional gap arthroplasty was accomplished and for 22 patients (45.8%) gap arthropasty was performed. Mean range of mouth opening before and after surgery was 10.3  3.9 and 33.9  5.2 in interpositional gap arthroplasty, 8.7  4.9 and 32.1  7.8 in gap arthropasty, respectively. The results showed that the range of mouth opening significantly increases after ankylosis surgery in both surgical approaches but improvement was less in interpositional gap arthroplasty. In regards to recurrence, results of interpositional gap arthroplasty were superior to gap arthropasty.